Analisis Faktor – Faktor Yang Mempengaruhi Sikap Kewirausahaan - Sallimah Ika Putri Malau; Zuhrinal M. Nawawi (ManBiz: Journal of Management and Business, 2023)
For students need to cultivate the words of entrepreneurship in order to support the life of competing at the world in the globalization. By looking at the phenomenon that occurs in the market share that more competition in the search for employment while the few available jobs resulting in unemployment. One way to alleviate unemployment is to entrepreneurship, by becoming entrepreneurs able to open new jobs to the community. However, establishing a business must be accompanied by a good entrepreneurial attitude ang right. By maximizing the entrepreneurial attitude can maximize also the things to be achieved. Being brave in making decisions by thingking about all aspects and can minimice loss and self-efficacy is one example of having an entrepreneurial attitude . and there are many other attitudes an entrepreneur must possess. The purpose of this research is (1) know what factors influences student entrepreneurship attitude, (2) to know the dominant factors that affect student entrepreneurship attitude. The method used in this study is literature review with analyzing of previous research in accordance with the needs of factors affecting entrepreneurial attitudes toward students. The results of the study found that there are factors that influence entrepreneurial attitude that is (1) self efficacy attitude (2) tenacious (3) dare to make decision (4) creative (5) independence (6) entrepreneurship education. Keywords: entrepreneurial attitudes, causes learning difficulties